The relationship between mental speed and mental abilities - Schubert, Anna-Lena (2016)
Mental speed is one often proposed candidate property of information processing affecting different cognitive abilities that may underlie individual differences in general intelligence. The aim of the present work was to expand the measurement of mental speed in individual differences research beyond the measurement of response times using state-of-the-art psychological and physiological methods. Based on two multivariate studies, this thesis demonstrates the benefits of a process-oriented approach to measuring mental speed. Moreover, the results show that on a behavioral level, mental speed can be considered as a one-dimensional trait, whereas one has to distinguish between the speed of early visual processing and higher-order processing on a physiological level. Finally, structural equation modeling revealed that on a behavioral level, general intelligence was associated with generally faster response times, whereas on a neurophysiological level, general intelligence was differentially related to earlier and later ERP latencies and was most strongly associated with ERP latencies reflecting the speed of higher-order processing. Taken together, ERP latencies explained about 85 percent of the variance in general intelligence, whereas response times explained only 19 percent. This result suggests that ERP latencies may provide a purer measurement of mental speed and that response times may be contaminated by additional processes such as motor planning and execution that are largely unrelated to general intelligence.
Publikationsbasierte Habilitationsschrift bestehend aus ? Beiträgen
Keywords: Hochschulschrift